Effect of lac-based formulations on incidence of Penicillum italicum on Kinnow fruits - R.R. SHARMA; S. SRIVASTAVA, DINESH SINGH*, P.C. SARKAR (Indian Phytopathology, 2008)
An experiment was conducted to find out the effect of lac-based formulations on incidence of Penicillium italicum on kinnow fruits and spoilage during storage at low temperature. Each fruit was punctured (10 holes) at four places by pinprick and dipped in emulsion (20%) of three different lac based formulation viz. FC -1, FC - 2 & FC - 3 and a stay fresh wax emulsion for 30 sec. For storage study, the fruits were treated with lac-based formulations and packed 30 fruits in each CFB box (5 ply) in 4 replicates for 75 days under cool chamber. Minimum incidence of P. italicum was found in stay fresh wax formulation (76.33%) followed by FC- 3. Moreover, minimum water soaked area was recorded in Stayfresh wax 9.24 em- followed by FC - 2 (9.81 cm2) after 5 days. Lac-based formulations inhibited growth of P. italicum on fruits. Spoilage of the fruits was significantly reduced by lac-based formulations during storage. These formulations did not deteriorate the quality of fruits up to 72 days under cool chamber. It may be used as coating agent to reduce the spoilage, shriveling and enhanced the shelf life of fruits.